The Ownership Problems of Overlaps in European Intellectual Property - Sousa e Silva, Nuno de Araujo (Munich Intellectual Property Law Center - MIPLC, 2014)
Intellectual Property rights are expanding and, thus, overlapping more than ever before. This poses challenges to a system devised as comprising a set of isolated compartments, each with its defined purpose.